A Analisis Pengaruh Temperatur Radiasi Matahari Terhadap Daya Luaran Solarcell 150 Wp Pematangsiantar: Analisis Pengaruh Temperatur Radiasi Matahari Terhadap Daya Luaran Solarcell 150 Wp Pematangsiantar - Simanullang, Ady Frenly; Panjaitan, Muktar Bahruddin; Manalu, Andriono (PendIPA Journal of Science Education, 2024)
By conducting an analysis of the influence of solar radiation temperature on the output power of a 150 Wp Pematangsiantar solar cell whose energy source comes from renewable energy, which is the sun, it is hoped to help the community's maximum needs by obtaining it directly from solar energy, in addition to being cheap, the use of solar energy has never exhausted, the maintenance cost of Solarcell is also very reasonable and not least it does not produce pollution that can damage the environment. This research aims to find out the performance of a 150 Wp solar panel in producing electricity in the form of current, voltage and power to charge a battery with a capacity of 12 V 7 Ah. Research data collection was carried out at 08.00 WIB - 17.00 WIB. The test to determine the current, voltage and power in this study uses several components, namely a 150 Wp solar panel, solar charger controller, battery, voltmeter and ammeter Testing of a 150 Wp solar panel as an alternative energy source and data taken every hour for 9 hours. The magnitude of the current and voltage from the solar panel can be read directly. Each solar panel has a different level of efficiency. In general, solar panels on private residential solar systems have a standard temperature of 25°C (77°F), with a general temperature range between 15°C and 35°C. It is in this temperature range that solar panels perform best. The limit point for solar panel efficiency is 65°C (149°F). Above this temperature, the performance efficiency of the solar system can be disrupted due to the drop in voltage produced.